Financing Higher Education: Who Pays, Who Benefits, and Who Should Pay for University Education in Uganda - Amutuhaire, Tibelius (https://doi.org/10.37284/eajes.5.1.625, 2022)
This paper analyses the existing modes of financing a university education in Uganda. Different parties, including the state, the student (household), donors, and the institution itself, are financing university education in Uganda. However, students are the primary source of funds for university education. Over the years, the fees charged to university students have been increasing to the extent that they are now becoming unaffordable to many students considering the current average annual household income. While the government is involved in funding university education, the level of involvement is unsatisfactory besides being discriminative. The existing government sponsorship scheme indirectly favours students from affluent families and denies access to poor students. The existing loan scheme focuses only on STEM courses and ignores students whose potentials are in the arts sector. However, in doing all this, the state uses taxpayers' money. Indirectly, poor households finance the education of students from affluent families while students from low-income families must struggle on their own. Therefore, it is submitted in this paper that the existing funding mechanism for university education in Uganda should be revisited and made fair, sustainable, and inclusive. The paper reviews literature relevant to the topic by adopting a general literature review methodology. It highlights the involvement of different partners that finance university education in Uganda and the benefits of university education. The paper submits that a better funding model for university education should involve the student, the university, and the state should take the leading role.